Silicon-mediated herbivore defence in a pasture grass under reduced and Anthropocene levels of CO2 - Biru, Fikadu N.; Cazzonelli, Christopher I.; Elbaum, Rivka; Johnson, Scott N. (Frontiers in Plant Science, 2023)
The uptake and accumulation of silicon (Si) in grass plants plays a crucial role in alleviating both biotic and abiotic stresses. Si supplementation has been reported to increase activity of defence related antioxidant enzyme which helps to reduce oxidative stress caused by reactive oxygen species (ROS) following herbivore attack. Atmospheric CO2 levels are known to affect Si accumulation in grasses; reduced CO2 concentrations increase Si accumulation whereas elevated CO2 concentrations often decrease Si accumulation. This can potentially affect antioxidant enzyme activity and subsequently insect herbivory, but this remains untested. We examined the effects of Si supplementation and herbivory by Helicoverpa armigera on antioxidant enzyme (catalase, CAT; superoxide dismutase, SOD; and ascorbate peroxidase, APX) activity in tall fescue grass (Festuca arundinacea) grown under CO2 concentrations of 200, 410, and 640 ppm representing reduced, ambient and elevated CO2 levels, respectively. We also quantified foliar Si, carbon (C) and nitrogen (N) concentrations and determined how changes in enzymes and elemental chemistry affected H. armigera relative growth rates and plant consumption. Rising CO2 concentrations increased plant mass and foliar C but decreased foliar N and Si. Si supplementation enhanced 2 activity of APX and SOD activity under the ranging CO2 regimes. Si accumulation and antioxidant enzyme activity were at their highest level under reduced CO2 conditions and their lowest level under future levels of CO2. The latter corresponded with increased herbivore growth rates and plant consumption suggesting that some grasses could become more susceptible to herbivory under projected CO2 conditions.